Estrategia de Inbound Marketing para fortalecer la comercialización de los productos artesanales de la panadería La Vienesa en la ciudad de Riobamba, fue aprobado - Ramírez Imues, Luis Fernando (2025)
This research focused on designing and implementing an Inbound Marketing strategy to strengthen the commercialization of artisanal products at La Vienesa bakery in Riobamba. The study arose from the need to modernize this traditional business's digital presence to better connect with contemporary audiences while maintaining the brand's artisanal essence. A mixed methodology was employed, combining quantitative and qualitative approaches. Data collection included surveys applied to a sample of 40 people, in-depth interviews with key bakery personnel, and a detailed analysis of existing social networks. This comprehensive approach allowed for a holistic understanding of the needs of both the business and its current and potential customers. The study results revealed significant patterns in consumer behavior and preferences. Facebook emerged as the most used digital platform with 76% regular usage, followed by Instagram and TikTok, both with 67.6% adoption. In terms of brand values, consumers showed strong appreciation for taste and quality (85.2% acceptance) and tradition (81.5%). Visual content showing appetizing products proved particularly effective, with 76% preference. The research culminated in the development of a comprehensive digital marketing strategy that includes various components: a complete brand manual establishing consistent visual guidelines, detailed publication prototypes for different social platforms, and a structured content plan that responds to the preferences identified in the study. The strategy was designed to maintain a balance between the modernization necessary for digital competitiveness and the preservation of the traditional values that have characterized La Vienesa.